Legal Protection on Notary Related with Deeds which Made in Process of Police Investigation - Nopi Siswanti; Sri Endah Wahyuningsih (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The notary office law and the notary code of ethics require that notaries in carrying out their duties as public officials, in addition to being subject to the position of a notary, they must comply with the professional code and must be responsible to the people they serve . Notaries who neglect all dignity of their positions apart from being subject to moral sanctions, being reprimanded or dismissed from their organization can also be fired from their positions as notaries. In fact, not all notaries act fairly, are impartial, and protect the interests of the parties. This study wants to see how the different roles of Indonesian police investigators in handling criminal acts committed by notaries after the Constitutional Court Decision No. in legal protection for notaries related to the deed he makes, then see how the model of legal protection for notaries who commit criminal acts related to the deed he made after the Constitutional Court Decision No 49 / PUU-X / 2012 and Ministerial Regulation and Human Rights Number 7 of 2016. Research it uses a socio legal approaches. Socio legal research examines the implementation or implementation of positive legal provisions in fact at any particular legal event that occurs in society in order to achieve predetermined goals.